2017
DOI: 10.1177/1071100717717264
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Ankle Position and Noninvasive Distraction on Arthroscopic Accessibility of the Distal Tibial Plafond

Abstract: OLTPs are often encountered in tandem with talar lesions, and safely achieving intra-articular working space through noninvasive distraction greatly improved arthroscopic accessibility.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 31 publications
(39 reference statements)
1
1
0
Order By: Relevance
“…The anteriormost fragments were accessed through either the medial or lateral malleolar approaches. Our results are consistent with Akoh et al, 3 who demonstrated the effectiveness of posterior arthroscopy in accessing the posterior 6 zones in combination with noninvasive distraction.…”
Section: Discussionsupporting
confidence: 93%
“…The anteriormost fragments were accessed through either the medial or lateral malleolar approaches. Our results are consistent with Akoh et al, 3 who demonstrated the effectiveness of posterior arthroscopy in accessing the posterior 6 zones in combination with noninvasive distraction.…”
Section: Discussionsupporting
confidence: 93%
“…1 ). Furthermore, a 3 × 3 grid was created to divide the distal tibial plafond into nine zones (1 = anteromedial, 2 = anterocentral, 3 = anterolateral, 4 = centromedial, 5 = central, 6 = centrolateral, 7 = posteromedial, 8 posterocentral, 9 = posterolateral) as previously described by other authors [ 29 , 30 ] (Fig. 2 ).…”
Section: Methodsmentioning
confidence: 99%